Financial Management and Firms’ Profitability: Evidence from Nigerian Manufacturing Listed Firms - Abiola, Olayiwola Kabirat; Othman, Intan Waheedah (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Nigerian manufacturing industry is one of the country's key economic growth engines. Since firms in the manufacturing sector are considered as high-risk ventures, they encounter significant difficulty in raising funds, especially from financial institutions. The manufacturing sector reported a significant decline in its economic activity and job creation compared to other sectors due to the difficulties faced by firms in attaining an optimal financial management strategy to support their business operations. In the attempt to identify optimal finance for maximizing firms’ profitability, this study aims to examine the relationship between financial management practices and the financial performance of quoted Nigerian manufacturing firms. A sample of 33 quoted Nigerian manufacturing companies from the year 2015 to 2018 were selected. A multivariate regression analysis was performed based on 132 firm-year observations, where it is documented that solvency, proxies by debt to assets ratio, is positively and significantly related to firm’s profitability. Results however revealed an insignificant relationship between liquidity and firm’s profitability. The findings of this study reveal that firms should sustain in being solvent in order to generate business growth and achieve set development goals. Besides being solvent, companies should manage their liquidity position effectively, thus enabling firms to reap competitive advantage. The findings support the trade-off theory, which claims that firm profitability increases as a firm’s debt increases, but only to the point where any further increases in the firms’ debt after it reaches its optimum level causes profitability to decline.